ICT, partnership and tourism, three factors united to promote the - Uribe Uran, Adriana; Messino Soza, Alexis (Cuadernos de Administración, 2010)
This article presents the experience gained by a research group from the Simon Bolivar University of Barranquilla-Colombia, after carrying out a project which consisted in the building of a communication system and the development of a group of strategies that will impulse the advantages of the Colombian Caribe as a touristic place, with the goal of improving the economic and social development of this Colombian region and making it an attractive place for national and foreign tourists, who, through the web page created as central strategy, could visit and enjoy the different tourism types it can offer: ecologic, adventure, health, cultural, beach and sun, among others. The research results showed the formation of a group of businessmen in the tourism sector, working in partnership under the support of a ICT’s platform that enables them to promote their services through collaborative designed web page and, the potential tourists to know the advantages of the Caribbean as a tourist destination